Dialogic reflective e-journaling: providing extra field-based support to special education preservice teachers by enhancing their critical reflection skills and transformative learning. Issue 3 (4th May 2019) - Carter, Pamela Weatherly; Kurtts, Stephanie A.
ABSTRACT: In light of the continual problem of attrition in the field of special education and the need for well-prepared new special education teachers, the purpose of this study was to examine how dialogic reflective e-journaling between the first author and undergraduate preservice teachers impacted the classroom decision-making as well as the transformative learning of these preservice teachers involved in a special education field-based experience in US schools. Performance feedback was given by the first author as part of the teacher preparation supports already in place for the field-based experience. Study findings revealed that dialogic e-journaling enhanced the reflective skills of the study participants when faced with classroom disorienting dilemmas and instigated a positive personal transformation in them as teachers.